Prevalence of syphilis and associated factors in the adult population treated at healthcare facilities in Vitória (ES), Brazil - Ferreira-Filho, Joaquim Batista; Gaspar, Pâmela Cristina; Bigolin, Alisson; Orletti, Maria do Perétuo Socorro Vendramini; Pereira, Fausto Edmundo Lima; Miranda, Angélica Espinosa (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: There are few population-sampling studies on the prevalence of syphilis in Brazil. Objectives: We aim to determine the seroprevalence of syphilis and identify factors associated with the infection in adult patients observed at six regional healthcare facilities in Vitória city, state of Espírito Santo, Brazil. Methods: A cross-sectional study was conducted between September 2010 and December 2011. For individuals included in the study, a Venereal Disease Research Laboratory (VDRL) test and two treponemal tests (immunochromatographic and IgG ELISA assays) were performed. Demographic data, history of sexually transmitted infections, and behavioral data were collected. Results: Of the 1,502 subjects included in the study, 47% were men and 53% were women. The mean age was 41.63±14.57 years. The prevalence of syphilis was (0.9%; 95%CI 0.4–1.3) when a diagnosis of syphilis was considered with VDRL titers equal to or greater than 1:8. However, the prevalence was higher (2.8%) when a positive VDRL test, regardless of the titer, was considered. A multivariate analysis showed a significant association between syphilis and homosexual or bisexual behavior [OR=6.80; 95%CI 1.00–46.20], prior history of sexually transmitted infection [OR=16.30; 95%CI 3.61–73.41], the presence of a tattoo [OR=6.21; 95%CI 1.49– 25.84], and cocaine use [OR=6.80; 95%CI 1.15–40.30]. The prevalence of positive treponemal test was 10.4%. Conclusion: The seroprevalence of active syphilis in this population was similar to that observed in other populational studies in Brazil. The high prevalence of positive treponemal tests may be due to the positive serological memory of a cured infection, but the results may also be due to cases of early or late syphilis that were not detected by the VDRL test.